Tallu Lino sebagai Landasan Kosmologi Arsitektur Bola (Rumah Tinggal) dan Landa’ (Lumbung Padi) di Kampong Pepandungan, Kabupaten Enrekang - Dwila Nur Haq; T. Yoyok Wahyu Subroto (Universitas Muhammadiyah Palembang, 2026)
This study aims to uncover the meaning of Tallu Lino as a cosmological foundation in shaping the traditional architecture of the Duri people, particularly in Bola (residences) and Landa’ (rice barns) in Kampong Pepandungan, Enrekang Regency. Tallu Lino, consisting of Lino Jiong (underworld), Lino Tau (middle world), and Lino Jao (upper world), is believed to form a cosmological framework that influences spatial structure, building orientation, and the relationship between domestic and storage spaces. The research employs a descriptive qualitative method with a phenomenological approach through field observations, in-depth interviews, and visual documentation. The findings show that Tallu Lino principles are reflected in the vertical spatial arrangement, the separation of functions between Bola and Landa’, and building orientation aligned with cosmic symbolism. This concept not only shapes physical structures but also embeds spiritual and sociocultural values. The study emphasizes the importance of understanding local cosmology as a foundation for preserving traditional architecture and guiding spatial planning based on indigenous wisdom.